(untitled) (GYMNASIUM, 2008)
The purpose of the evaluation in raising the sporting performances is underlined by the conception of team-work regarding the objectives, the purpose and the functions of the evaluation, as well as the operations, methods and strategies of evaluation of the sportsmen’s behavior. The choosing of the most adequate methods and strategies of evaluation gives the possibility of a complex, true and sensitive evaluation at the individual differences between sportsmen, their timely joining might lead to relevant information regarding the results and progresses registered in training and competitions. An objective evaluation stimulates the sportsmen, increases their trust in obtaining some superior results, gives them a feed-back of the level achieved in completing the objectives, the sportsman adjusts his effort, optimizes the tempo of the training, consolidates or modifies the proceedings and methods of training.